Memory B Cells in Pregnancy Sensitization - Nellore, Anoma; Killian, John T.; Porrett, Paige M. (Frontiers in Immunology, 2021)
Memory B cells play an important role in immunity to pathogens as these cells are poised to rapidly differentiate into antibody-secreting cells upon antigen re-encounter. Memory B cells also develop over the course of HLA-sensitization during pregnancy and transplantation. In this review, we discuss the potential contribution of memory B cells to pregnancy sensitization as well as the impact of these cells on transplant candidacy and outcomes. We start by summarizing how B cell subsets are altered in pregnancy and discuss what is known about HLA-specific B cell responses given our current understanding of fetal antigen availability in maternal secondary lymphoid tissues. We then review the molecular mechanisms governing the generation and maintenance of memory B cells during infection – including the role of T follicular helper cells - and discuss the experimental evidence for the development of these cells during pregnancy. Finally, we discuss how memory B cells impact access to transplantation and transplant outcomes for a range of transplant recipients.